2013
DOI: 10.1108/el-03-2011-0044
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of university student web searching competency by a task‐based online test

Abstract: PurposeThe purpose of this paper is to assess student web searching competency. The paper aims to determine varying levels of university student competency in web searches and to investigate and compare their competency levels of searching academic and daily‐life tasks.Design/methodology/approachThe study adopted a quantitative research method of giving study participants a controllable experiment, a task‐based online test (TBOT), to evaluate web searching competency based on student searching performance. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Regarding the methods of evaluating information literacy, most scholars use only self-designed questionnaires that consist of self-assessments with closed-ended test questions (Pinto et al, 2019 ). Other scholars have combined interviews (Walters et al, 2020 ), experiments (Ding & Ma, 2013 ) and other survey methods to evaluate the developmental level of information literacy. However, these methods lack enthusiasm and flexibility, and the data collection process requires substantial cooperation from users, which is time-consuming and laborious.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the methods of evaluating information literacy, most scholars use only self-designed questionnaires that consist of self-assessments with closed-ended test questions (Pinto et al, 2019 ). Other scholars have combined interviews (Walters et al, 2020 ), experiments (Ding & Ma, 2013 ) and other survey methods to evaluate the developmental level of information literacy. However, these methods lack enthusiasm and flexibility, and the data collection process requires substantial cooperation from users, which is time-consuming and laborious.…”
Section: Discussionmentioning
confidence: 99%
“…Sin (2015) identified a need for ELIL training for international students in relation to legal and financial information and found that search and evaluation skills as well as individual problem solving styles and affective factors require more attention and support by IL professionals who should be involved in cultivating students' life skills. Ding and MA (2013), in an earlier study of 141 undergraduate and graduate students from Wuhan University in China have similarly reported that IL education should incorporate comprehensive web searching competencies that address knowledge and techniques related to both academic and daily life search tasks.…”
mentioning
confidence: 99%
“…The concepts of information searching and using, although related, are different. Since its inception (Kuhlthau, 1991), research on information searching has been a permanent topic in the literature on IL (Gross and Latham, 2008;Rich, 2008;Ding and Ma, 2013;Leichner et al, 2014;Rieh et al, 2016;Savolainen, 2018). There are other related concepts, such a user, user need, and seeking behaviour (Wilson, 2008;Subhash Reddy, Krishnamurthy and Asundi, 2018).…”
Section: On the Uncovered Factorsmentioning
confidence: 99%
“…In fact, this research deals with all the issues involved in IL. Among them are those of searching (Rich, 2008; Ding and Ma, 2013; Rieh et al , 2016), evaluation (Hjørland, 2012), processing (Savolainen, 2009), ethics (Samek, 2010), communication (ACRL, 2013), technological processing (Markauskaite, 2007) and computer technology (Malliari et al , 2012). In any case, IL abilities relate to both “declarative as well as procedural knowledge [since they] can be seen as predictor of competency” (Zylka, 2012: 778).…”
Section: Literature Reviewmentioning
confidence: 99%